2010
DOI: 10.1007/s00221-010-2447-4
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal anesthetic protocol for measurements of cerebral autoregulation in spontaneously breathing mice?

Abstract: Autoregulation, an important feature of the cerebral circulation, is affected in many diseases. Since genetically modified mice are a fundamental tool in biomedical research, including neuro(bio)logy also in this specie measurements of cerebral autoregulation (CA) are mandatory. However, this requires anesthesia that unfortunately significantly impacts cerebral perfusion and consequently might distort CA measurements directly or by altering arterial pCO(2). The latter can be avoided by artificial ventilation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 37 publications
(62 reference statements)
0
42
0
Order By: Relevance
“…This combination has a relatively small effect on blood pressure and vessel reactivity 11 . In contrast, isoflurane, a widely used anesthetic in SAH research, leads to peripheral vasodilation, severely impaired cerebral autoregulation 13 , and low blood pressure immediately after SAH 12 , findings which are not regularly associated with the early pathophysiology of SAH in humans. Hence, the use of an anesthetic protocol that does not disturb posthemorrhagic pathophysiology is an important prerequisite for a valid experimental SAH model.…”
Section: End Of Experimentsmentioning
confidence: 96%
“…This combination has a relatively small effect on blood pressure and vessel reactivity 11 . In contrast, isoflurane, a widely used anesthetic in SAH research, leads to peripheral vasodilation, severely impaired cerebral autoregulation 13 , and low blood pressure immediately after SAH 12 , findings which are not regularly associated with the early pathophysiology of SAH in humans. Hence, the use of an anesthetic protocol that does not disturb posthemorrhagic pathophysiology is an important prerequisite for a valid experimental SAH model.…”
Section: End Of Experimentsmentioning
confidence: 96%
“…33 However, both compounds tend to increase CBF and to disrupt cerebral autoregulation in animals. 34 In summary, CBF and cerebral blood volume (CBV) are typically decreased by anaesthesia produced by propofol and increased by ketamine and isoflurane/halothane in animals used for PET neuroimaging. 30 12,20,45,46 These changes are particularly important in quantitative kinetic analysis of brain glucose metabolism, although reduced neural activity caused by anaesthesia may also affect the outcome of PET studies on new drugs such as CNS stimulants.…”
Section: Cbf and Cerebral Blood Volumementioning
confidence: 99%
“…Because anaesthesia can inhibit an animal's homeostasis, which indirectly can influence PET results, 33 careful monitoring is important. 34 Hypothermia can develop, for …”
mentioning
confidence: 99%
“…Moreover, vasoconstriction was favored in parenchymal arterioles with minimal or no tone (Blanco et al, 2008). Lastly, for in vivo studies, anesthesia has been shown to significantly alter astrocyte activity (Thrane et al, 2012) as well as cerebrovascular function (Ayata et al, 2004, Kuga et al, 2009, Wang et al, 2010). Thus, careful considerations of these two parameters must be made when interpreting in vivo observations.…”
Section: Introductionmentioning
confidence: 99%